INTER-STAKEHOLDER COMMUNICATION IN THE DIGITAL POVERTY ALLEVIATION PROGRAM IN INDONESIA - RR Roosita Cindrakasih,; Deby Puspitaningrum,; Marlina Rahmi Shinta P,; Adityo Fajar, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Digital transformation brings new opportunities and challenges to poverty alleviation efforts in Indonesia. The government, private sector, and civil society play a crucial role in creating an inclusive ecosystem that ensures equitable digital access. This study aims to analyze communication patterns among stakeholders in digital poverty alleviation programs, highlighting coordination, collaboration, and emerging communication barriers. The research approach employed descriptive qualitative methods with in-depth interviews and analysis of inclusive digital policy documents. The results indicate that communication among stakeholders remains vertical and fragmented, with the government dominating and local communities limited in its involvement. Effective cross-sector collaboration occurs when participatory communication mechanisms, information transparency, and trust between actors are in place. This study confirms that adaptive and inclusive strategic communication is a key factor in the success of digital poverty alleviation programs in Indonesia